Physical activity levels after treatment for breast cancer: Two-year follow-up. (August 2018) - De Groef, An; Geraerts, Inge; Demeyer, Heleen; Van der Gucht, Elien; Dams, Lore; de Kinkelder, Carlijn; Dukers-van Althuis, Sanne; Van Kampen, Marijke; Devoogdt, Nele
Abstract: Objectives: Breast cancer treatment can have a considerable large and prolonged impact on activity levels of breast cancer survivors. Therefore, the aim of the present study was to investigate the change in total physical activity level and occupational, sport and household activity levels of breast cancer survivors from preoperatively up to 24 months after breast cancer surgery. Additionally, predictive factors for this change were investigated. Methods: Patients with primary breast cancer (n = 267) filled in the Flemish Physical Activity Computerized Questionnaire (FPACQ) before surgery and 1, 3, 6, 12 and 24 months after surgery. Patient-, disease- and treatment-related factors were analyzed as predictive factors for change in physical activity. Results: Two years after surgery, all activity levels (total, occupational, sport and household) were still significantly lower compared to preoperative values. After the first 12 months, no significant improvements were seen for none of the activity levels, except for the occupational activity. Conclusions: Two years after breast cancer surgery, physical activity levels are still significantly lower compared to pre-operative values. Based on this limited recovery, it seems important to monitor physical activity levels in breast cancer patients and advice these patients to stay active after surgery and return to pre-operative activity levels in the long term as well. This study indicates the importance of long term monitoring and subsequently coaching of physical activity after breast cancer surgery. Highlights: Two years after breast cancer surgery, physical activity levels are not yet recovered. Coaching breast cancer survivors may be needed to return to pre-operative activity levels. Long term monitoring of physical activity is warranted in breast cancer survivors.